Direct and size‐mediated effects of temperature and ration‐dependent growth rates on energy reserves in juvenile anadromous alewives (Alosa pseudoharengus). Issue 4 (23rd June 2021) - Guo, Lian W.; McCormick, Stephen D.; Schultz, Eric T.; Jordaan, Adrian
ABSTRACT: Growth rate and energy reserves are important determinants of fitness and are governed by endogenous and exogenous factors. Thus, examining the influence of individual and multiple stressors on growth and energy reserves can help estimate population health under current and future conditions. In young anadromous fishes, freshwater habitat quality determines physiological state and fitness of juveniles emigrating to marine habitats. In this study, the authors tested how temperature and food availability affect survival, growth and energy reserves in juvenile anadromous alewives ( Alosa pseudoharengus ), a forage fish distributed along the eastern North American continent. Field‐collected juvenile anadromous A. pseudoharengus were exposed for 21 days to one of two temperatures (21°C and 25°C) and one of two levels of food rations (1% or 2% tank biomass daily) and compared for differences in final size, fat mass‐at‐length, lean mass‐at‐length and energy density. Increased temperature and reduced ration both led to lower growth rates, and the effect of reduced ration was greater at higher temperature. Fat mass‐at‐length decreased with dry mass, and energy density increased with total length, suggesting size‐based endogenous influences on energy reserves. Lower ration also directly decreased fat mass‐at‐length, lean mass‐at‐length and energy density. Given the fitness implications of size and energy reserves, temperature and food availability should be considered important indicators of nursery habitat quality and incorporated in A. pseudoharengus life‐history models to improve forecasting of population health under climate change.